Research progress on Brassicaceae plants: a bibliometrics analysis - Zhou, Ruixue; Qin, Xinsheng; Hou, Junjun; Liu, Yining (Frontiers in Plant Science, 2024)
The Brassicaceae is a worldwide family that produces ornamental flowers, edible vegetables, and oilseed plants, with high economic value in agriculture, horticulture, and landscaping. This study utilized the Web of Science core dataset and the CiteSpace measurement tool to conduct a quantitative visualization analysis of the number of papers, authors, institutions, and countries related to Brassicaceae plants in 3139 English core journals from 2002-2022. The keywords and references were divided into two phases: Phase 1 (2002-2011) and Phase 2 (2012-2022) for quantitative and qualitative analysis. The results showed: An average annual publication volume of 149 articles, with an overall fluctuating upward trend; the research force was mainly led by Professor Ihsan A. Al-shehbaz from Missouri Botanical Garden; and the United States had the highest number of publications. In the first phase, research focused on the phylogeny of Brassicaceae plants, while the second phase delved into diverse research based on previous studies, research in areas such as polyploidy, molecular technique, physiology, and hyperaccumulator has been extended. Based on this research, we propounded some ideas for future studies on Brassicaceae plants and summarized the research gaps.